Resilient sustainable cities. A future. - (:unkn) unknown (Routledge, 2014)
In the next 30 years cities will face their biggest challenges yet, as a result of long term, or "slow burn" issues: population growth will stretch to the breaking point urban infrastructure and service capacity; resource scarcity, such as peak oil; potable water and food security, will dramatically change what we consume and how; environmental pressures will change how we live and where and; shifting demographic preferences will exacerbate urban pressures. Cities can't keep doing what they've always done and cope - we need to change current urban development to achieve resilient, sustainable cities. The book provides practical and conceptual insights for practitioners, researchers and students on how to deliver cities which are resilient to "slow burn" issues and achieve sustainability. The book is organized around three overarching themes: pathways to the future, innovation to deliver the future, leadership and governance issues. It includes a variety of perspectives conveyed through international case studies and examples of cities that have transformed for a sustainable future, exploring their successes and failures to ensure that readers are left with ideas on how to turn their city into a resilient sustainable city for the future.
Keywords: Stadtentwicklungsplanung; Stadtregion; Stadtentwicklung; Stadtstruktur; Innovation; Stadtverkehr; Bebauung; Abfallwirtschaft; Siedlungsstruktur; Strukturwandel; Nachhaltigkeit; Nachhaltige Entwicklung; Handlungsfeld; Stadtumbau; Resilienz; Transformation; Governance; Fallbeispiel